2023
DOI: 10.1007/s11071-023-08447-1
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent control of cardiac rhythms using artificial neural networks

Abstract: Cardiac rhythms are related to heart electrical activity, being an essential aspect of the cardiovascular physiology. Usually, these rhythms are represented by electrocardiograms (ECGs) that are useful to detect cardiac pathologies. This paper investigates the control of cardiac rhythms in order to induce normal rhythms from pathological responses. The strategy is based on the electrocardiograms and considers different pathologies. An intelligent controller is proposed considering the ECG as the observable var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…With two unknowns u and v, an additional relationship is imposed on equation (13), which gives us equation (14). With = U u 3 and = V v .…”
Section: Fixed Points Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With two unknowns u and v, an additional relationship is imposed on equation (13), which gives us equation (14). With = U u 3 and = V v .…”
Section: Fixed Points Analysismentioning
confidence: 99%
“…Physiologically, normal compliance of the heart depends on the regularity of the system. References [9][10][11][12][13] have shown that the construction of synthetic ECGs can reveal a variety of responses, including normal and pathological rhythms. In a similar vein, Norbert Wiener and Arturo Rosenblueth, in their work on the mathematical formulation of the problem of impulse conduction in a network of connected excitable elements, notably in cardiac muscle, demonstrated the importance of the spatial role of depolarization waves on cardiac tissue, beyond just the SA and AV nodes, and the His bundles and Purkinje fibers [14].…”
Section: Introductionmentioning
confidence: 99%
“…These non-linear oscillators include the FitzHugh and Nagumo oscillato [11], the Hodgkin-Huxley oscillator [12], the Grudzinski-Zebrowski oscillator [13], the Hartley model [14], the Colpitts model [15], the Tchitnga oscillator [16], etc The results obtained thanks to the richness of their dynamics have contributed to major advances in many areas of research, both fundamental and engineering. [8,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%